Cardiorespiratory response and energy system contribution during speed endurance workout in a highly trained sprinter: A preliminary report - Kusy, K.; Zarebska, E.; Ciekot-Soltysiak, M.; Janowski, M.; Zielinski, J. (Journal of Kinesiology and Exercise Sciences, 2015)
Purpose. Assessment of the physiological response to individually programmed speed endurance track session in a highly trained sprinter. Basic procedures. One male sprinter, aged 23 years, a member of the Polish national team, was examined. He underwent the ergospirometric graded exercise test (GXT) to assess aerobic capacity and maximum blood lactate (LA). In the competition period, the same variables were measured during repeated sprints (60 m, 60 m, 100 m and 120 m) on a standard athletic track using a mobile wireless ergospirometer. The energy contribution from aerobic and anaerobic metabolism was calculated from exercise oxygen uptake (VO2), fast component of post-exercise oxygen consumption and net post-exercise blood lactate concentration. Main findings. Peak values relative to those obtained during GXT were: 80% for minute ventilation (VE), 111% for breathing frequency (BF), 103% for tidal volume (VT), 79% for peak VO2, 90% for heart rate (HR) and 84% for oxygen pulse (VO2/HR). Posteffort peak values were attained at different times: VE 37-46 s, BF 23-34 s, VT 38-67 s, VO2 46-89 s, HR 36-48 s and VO2/HR 45-77 s. Peak LA after the last sprint reached 147% of the GXT maximum. The proportions of aerobic, anaerobic alactic and anaerobic lactic acid energy sources were approximately 11.1%, 46.4% and 42.5%, respectively. Conclusions. The athlete showed typical contribution of aerobic and anaerobic energy delivery during the speed endurance workout. We support the notion that specific speed endurance exercise rely both on anaerobic and aerobic metabolism. Monitoring and control of the actual track sessions using high-tech equipment may help coaches and athletes to determine optimal workout parameters.